On the value guidelines of russian students and on fostering the moral foundations of society - Roman G. Strongin; Aleksandr V. Petrov (Высшее образование в России)
Advancement of moral development as a function of state educational establishments to a new qualitative level is under consideration. The purpose is to facilitate the shaping of the young generation moral values ensuring the progressive development of Russian society.